Evaluation of an integrated WRF-Chem framework for air quality forecasting and source attribution in Jaipur, India - Prafull P. Yadav; Gaurav Govardhan; Rajmal Jat; Rajesh Kumar; Bhuvnesh Mathur; Shilpi Sharma; Priyanshi Tiwari; Sachin D. Ghude (Environmental Monitoring and Assessment, 2026)

Decoding of physiological and molecular mechanisms for breeding of drought tolerant crops - Ratnakumar Pasala; Brij Bihari Pandey; ChLN Manikanta; Arun K. Shanker; K. Ramesh; Subramaniam Geethanjali; Amaranatha R. Vennapusa; Kalpalatha Melmaiee; Pooja Srivastava; Amber Gupta; Yogeshwar Singh; Sanket J. More; et al. (Plant Physiology Reports, 2025)

Treatment of textile effluent by electrocoagulation in a novel reactor to mitigate environmental pollution - P. Agarwal; V. K. Sangal; S. Mathur (International Journal of Environmental Science and Technology, 2025)

Deciphering the effect of Chlorella minutissima incorporation in gluten-free millet cookies: Physical and functional properties - Koushalya Selvaraju; Megha Mathur; Satheeshkanth SSM; Jatindra K. Sahu; P. Hariprasad; Anushree Malik (Algal Research, 2024)

S17-02: The Long-term Impact of Perinatal Exposures on Susceptibility to Immune-mediated Diseases - K.A. Rychlik; E.J. Illingworth; S.E. Attreed; S.S. Sanchez; A. Grant-Alfieri; M.C. Rodriguez Steube; A. Mathur; I.F. Sanchez; C. Tang; M. Suresh; G. Lopez-Cecetaite; P. Sadhukhan; et al. (Toxicology Letters, 2023)

Mutation spectrum and enzyme profiling of G6PD deficiency in neonates of north India: a prospective study - Upasana Bhattacharyya; Preeti Deswal; Sunil Kumar Polipalli; Diksha Sharma; Manpreet Kaur; Madhulika Kabra; Neerja Gupta; Ramesh Agarwal; A. K. Deorari; V. K. Paul; Shevendru Roy; R. K. Sanjeev; et al. (Journal of Genetics, 2023)

Evaluation of the Morphological and Biological Functions of Vascularized Microphysiological Systems with Supervised Machine Learning - James J. Tronolone; Tanmay Mathur; Christopher P. Chaftari; Abhishek Jain (Annals of Biomedical Engineering, 2023)

A novel QTL linked to asparagine synthetase gene for stem height increment in oil palm (E. guineensis Jacq.) identified and validated through integrated genomic approaches - B. Kalyana Babu; R. K. Mathur; G. Ravichandran; P. Anitha; H. P. Bhagya; M. V. B. Venu (Euphytica, 2023)

Investigation of metasomatism using Cu, Zn and Fe stable isotopes: Rodingitization of mafic and ultramafic rocks in ophiolites from northern Greece - N. Zaronikola; V. Debaille; A. Rogkala; P. Petrounias; R. Mathur; S. Decrée; P. Pomonis; K. Hatzipanagiotou; B. Tsikouras (Lithos, 2023)

Cu isotopes in groundwater for hydrogeochemical mineral exploration: A case study using the world-class Mount Isa Cu–Pb–Zn deposit (Australia) - B. Mahan; R. Mathur; I. Sanislav; P. Rea; P. Dirks (Applied Geochemistry, 2023)

Epigenetic modulation and apoptotic induction by a novel imidazo-benzamide derivative in human lung adenocarcinoma cells - Amrutha Arjunan; Sankar Pajaniradje; Arul Prakash Francis; Srividya Subramanian; Sathyapriya Chandramohan; D. Parthasarathi; Ayyiliath M. Sajith; M. Syed Ali Padusha; P. P. Mathur; Rukkumani Rajagopalan (DARU Journal of Pharmaceutical Sciences, 2021)

Phenomics, genomics of oil palm (Elaeis guineensis Jacq.): way forward for making sustainable and high yielding quality oil palm - B. Kalyana Babu; R. K. Mathur; P. Anitha; G. Ravichandran; H. P. Bhagya (Physiology and Molecular Biology of Plants, 2021)

An update and perspectives on the use of promoters in plant genetic engineering - Divya Kummari; Sudhakar Reddy Palakolanu; P B Kavi Kishor; Pooja Bhatnagar-Mathur; Prasanth Singam; Vincent Vadez; Kiran K Sharma (Journal of Biosciences, 2020)

Identification of QTLs in oil palm (Elaeis guineensis Jacq.) using SSR markers through association mapping - H. P. Bhagya; B. Kalyana Babu; P. M. Gangadharappa; Mahantesha B. N. Naika; D. Satish; R. K. Mathur (Journal of Genetics, 2020)

Comparing transformation pathways across major economies - R. Schaeffer; A. Köberle; H. L. van Soest; C. Bertram; G. Luderer; K. Riahi; V. Krey; D. P. van Vuuren; E. Kriegler; S. Fujimori; W. Chen; C. He; et al. (Climatic Change, 2020)

Isolation and functional characterization of three abiotic stress-inducible (Apx, Dhn and Hsc70) promoters from pearl millet (Pennisetum glaucum L.) - Kummari Divya; P. B. Kavi Kishor; Pooja Bhatnagar-Mathur; Prashanth Singam; Kiran K. Sharma; Vincent Vadez; Palakolanu Sudhakar Reddy (Molecular Biology Reports, 2019)

Calcium ionophore enhanced developmental competence and apoptotic dynamics of goat parthenogenetic embryos produced in vitro - Diksha Dua; D. Nagoorvali; M.S. Chauhan; P. Palta; P. Mathur; M. K. Singh (In Vitro Cellular & Developmental Biology - Animal, 2019)

Day-1 INSAT-3DR Vicarious Calibration Using Reflectance-Based Approach Over Great Rann of Kutch - Piyushkumar N. Patel; K. N. Babu; R. P. Prajapati; Vikram Sitapara; A. K. Mathur (Journal of the Indian Society of Remote Sensing, 2018)

Indian spinach: an underutilized perennial leafy vegetable for nutritional security in developing world - Ajeet Singh; Pradeep K. Dubey; Rajan Chaurasiya; Nitin Mathur; Gangesh Kumar; Sujeet Bharati; P. C. Abhilash (Energy, Ecology and Environment, 2018)

Aegle marmelos differentially affects hepatic markers of glycolysis, insulin signalling pathway, hypoxia, and inflammation in HepG2 cells grown in fructose versus glucose-rich environment - H. Aggarwal; J. Nair; P. Sharma; R. Sehgal; U. Naeem; P. Rajora; R. Mathur (Molecular and Cellular Biochemistry, 2018)

Potential of Crop Residue and Fertilizer on Enrichment of Carbon Pools in Upland Soils of Subtropical India - P. K. Ghosh; K. K. Hazra; M. S. Venkatesh; K. K. Singh; Narendra Kumar; R. S. Mathur (Agricultural Research, 2016)

Layout and Component Size Optimization of Sewer Network Using Spanning Tree and Modified PSO Algorithm - Praveen K. Navin; Yogesh P. Mathur (Water Resources Management, 2016)

DREB1A overexpression in transgenic chickpea alters key traits influencing plant water budget across water regimes - Krithika Anbazhagan; Pooja Bhatnagar-Mathur; Vincent Vadez; Srinivas Reddy Dumbala; P. B. Kavi Kishor; Kiran K. Sharma (Plant Cell Reports, 2015)

Monitoring hospital wastewaters for their probable genotoxicity and mutagenicity - Pratibha Sharma; N. Mathur; A. Singh; M. Sogani; P. Bhatnagar; R. Atri; S. Pareek (Environmental Monitoring and Assessment, 2015)

A multi-step phosphorelay two-component system impacts on tolerance against dehydration stress in common wheat - Vijay Gahlaut; Saloni Mathur; Raman Dhariwal; Jitendra P. Khurana; Akhilesh K. Tyagi; Harindra S. Balyan; Pushpendra K. Gupta (Functional & Integrative Genomics, 2014)

28-Homobrassinolide: a novel oxysterol transactivating LXR gene expression - R. Premalatha; K. Srikumar; D. Vijayalaksmi; G. N. Kumar; P. P. Mathur (Molecular Biology Reports, 2014)

Acetamide hydrolyzing activity of Bacillus megaterium F-8 with bioremediation potential: Optimization of production and reaction conditions. - Monika Sogani; Prakash P. Bakre; Nupur Mathur; Pratibha Sharma; Pradeep Bhatnagar (Environmental Science and Pollution Research, 2014)

A Comparative Study of the Sensitivities of Salmonella typhimurium Strains TA 98, TA 100 and TA 102 to Hospital Waste Waters - Preeti Gupta; P. Mathur; N. Mathur; B. Aarya (Bulletin of Environmental Contamination and Toxicology, 2014)

Study of equatorial regions of Moon with the help of backscattering coefficient obtained from LRO data - O P N CALLA; SHUBHRA MATHUR; MONIKA JANGID (Journal of Earth System Science, 2014)

Computational analysis of CYP3A4-mediated metabolism to investigate drug interactions between anti-TB and anti-HIV drugs in HIV/TB co-infection - Jayakanthan Mannu; Pranitha Jenardhanan; Premendu P. Mathur (Medicinal Chemistry Research, 2014)

A new scenario framework for climate change research: the concept of shared socioeconomic pathways - Brian C. O’Neill; Elmar Kriegler; Keywan Riahi; Kristie L. Ebi; Stephane Hallegatte; Timothy R. Carter; Ritu Mathur; Detlef P. van Vuuren (Climatic Change, 2014)

A new scenario framework for Climate Change Research: scenario matrix architecture - Detlef P. van Vuuren; Elmar Kriegler; Brian C. O’Neill; Kristie L. Ebi; Keywan Riahi; Timothy R. Carter; Jae Edmonds; Stephane Hallegatte; Tom Kram; Ritu Mathur; Harald Winkler (Climatic Change, 2014)
This paper describes the scenario matrix architecture that underlies a framework for developing new scenarios for climate change research. The matrix architecture facilitates addressing key questions related to current climate research and policy-making: identifying the effectiveness of different adaptation and mitigation strategies (in terms of their costs, risks and other consequences) and the possible trade-offs and synergies. The two main axes of the matrix are: 1) the level of radiative forcing of the climate system (as characterised by the representative concentration pathways) and 2) a set of alternative plausible trajectories of future global development (described as shared socio-economic pathways). The matrix can be used to guide scenario development at different scales. It can also be used as a heuristic tool for classifying new and existing scenarios for assessment. Key elements of the architecture, in particular the shared socio-economic pathways and shared policy assumptions (devices for incorporating explicit mitigation and adaptation policies), are elaborated in other papers in this special issue.

A new scenario framework for climate change research: background, process, and future directions - Kristie L. Ebi; Stephane Hallegatte; Tom Kram; Nigel W. Arnell; Timothy R. Carter; Jae Edmonds; Elmar Kriegler; Ritu Mathur; Brian C. O’Neill; Keywan Riahi; Harald Winkler; Detlef P. Van Vuuren; et al. (Climatic Change, 2014)
The scientific community is developing new global, regional, and sectoral scenarios to facilitate interdisciplinary research and assessment to explore the range of possible future climates and related physical changes that could pose risks to human and natural systems; how these changes could interact with social, economic, and environmental development pathways; the degree to which mitigation and adaptation policies can avoid and reduce risks; the costs and benefits of various policy mixes; and the relationship of future climate change adaptation and mitigation policy responses with sustainable development. This paper provides the background to and process of developing the conceptual framework for these scenarios, as described in the three subsequent papers in this Special Issue (Van Vuuren et al., 2013; O’Neill et al., 2013; Kriegler et al., Submitted for publication in this special issue). The paper also discusses research needs to further develop, apply, and revise this framework in an iterative and open-ended process. A key goal of the framework design and its future development is to facilitate the collaboration of climate change researchers from a broad range of perspectives and disciplines to develop policy- and decision-relevant scenarios and explore the challenges and opportunities human and natural systems could face with additional climate change.

Semen quality of environmentally exposed human population: the toxicological consequence - Niraj Pant; A. B. Pant; P. K. Chaturvedi; M. Shukla; N. Mathur; Y. K Gupta; D. K. Saxena (Environmental Science and Pollution Research, 2013)

Health care industries: potential generators of genotoxic waste - Pratibha Sharma; Manish Kumar; N. Mathur; A. Singh; P. Bhatnagar; M. Sogani (Environmental Science and Pollution Research, 2013)

OPTIMAL WATER SCHEDULING IN IRRIGATION CANAL NETWORK USING PARTICLE SWARM OPTIMIZATION - Anil W. Pawde; Yogesh P. Mathur; Rajesh Kumar (Irrigation and Drainage, 2013)
Rotational water scheduling in the irrigation canal network is a problem of preparing the operation schedule of lateral canals to deliver the required quantity of water to the irrigation fields under it within the rotational period as per the crop water requirement. The important objectives of a rotational canal schedule are to minimize capacity of canal and operational stages of the head gate of supply canal; subject to canal capacity constraint. In the present paper, to achieve these objectives, the decision variables considered are rate of water delivery and start time of delivery points, which are determined by the model within the specified range. Particle swarm optimization has been used to solve the problem and applied on the two water scheduling problems for generating the optimal water schedule. The schedules generated by the model shows that the inflow hydrographs of supply canals are approximately constant throughout the rotation period with least operation of canal head gate which could results in minimum conveyance losses. This model could be used for the preparation of a rotational schedule for the existing irrigation canal system and a more economic design of the supply canals for a new irrigation canal system. Copyright © 2013 John Wiley & Sons, Ltd.

Pathogen-derived resistance using a viral nucleocapsid gene confers only partial non-durable protection in peanut against peanut bud necrosis virus - S. Chander Rao; P. Bhatnagar-Mathur; P. Lava Kumar; A. Sudarshan Reddy; Kiran K. Sharma (Archives of Virology, 2013)

Modeling, docking, simulation, and inhibitory activity of the benzimidazole analogue against β-tubulin protein from Brugia malayi for treating lymphatic filariasis - Om Prakash Sharma; Archana Pan; S. L. Hoti; Ankush Jadhav; Muthu Kannan; Premendu P. Mathur (Medicinal Chemistry Research, 2012)

Biotransformation of amide using Bacillus sp.: isolation strategy, strain characteristics and enzyme immobilization - M. Sogani; N. Mathur; P. Bhatnagar; P. Sharma (International Journal of Environmental Science and Technology, 2012)

Growth, alkaloid production, rol genes integration, bioreactor up-scaling and plant regeneration studies in hairy root lines of Catharanthus roseus - P Verma; A K. Mathur; K Shanker (Plant Biosystems, 2012)

Obesity and Abdominal Adiposity in Diabetic Dyslipidemia - Manisha Sankhla; Keerti Mathur; Jai Singh Rathor; Sushila Gahlot; R. P. Agrawal (Indian Journal of Clinical Biochemistry, 2011)

Yellowstone Lake: high‐energy geochemistry and rich bacterial diversity - Scott Clingenpeel; Richard E. Macur; Jinjun Kan; William P. Inskeep; Dave Lovalvo; John Varley; Eric Mathur; Kenneth Nealson; Yuri Gorby; Hongchen Jiang; Toben LaFracois; Timothy R. McDermott (Environmental Microbiology, 2011)
Summary Yellowstone Lake is central to the balanced functioning of the Yellowstone ecosystem, yet little is known about the microbial component of its food chain. A remotely operated vehicle provided video documentation ( http://www.tbi.montana.edu/media/videos/ ) and allowed sampling of dilute surface zone waters and enriched lake floor hydrothermal vent fluids. Vent emissions contained substantial H 2 S, CH 4 , CO 2 and H 2 , although CH 4 and H 2 levels were also significant throughout the lake. Pyrosequencing and near full‐length sequencing of Bacteria 16S rRNA gene diversity associated with two vents and two surface water environments demonstrated that this lake contains significant bacterial diversity. Biomass was size‐fractionated by sequentially filtering through 20‐µm‐, 3.0‐µm‐, 0.8‐µm‐ and 0.1‐µm‐pore‐size filters, with the > 0.1 to Acidobacteria , Actinobacteria , Bacteroidetes , α‐ and β‐ Proteobacteria and Cyanobacteria , with 21 other phyla represented at varying levels. Surface waters were dominated by two phylotypes: the Actinobacteria freshwater ac I group and an α‐ Proteobacteria clade tightly linked with freshwater SAR11‐like organisms. We also obtained evidence of novel thermophiles and recovered Prochlorococcus phylotypes (97–100% identity) in one near surface photic zone region of the lake. The combined geochemical and microbial analyses suggest that the foundation of this lake's food chain is not simple. Phototrophy presumably is an important driver of primary productivity in photic zone waters; however, chemosynthetic hydrogenotrophy and methanotrophy are likely important components of the lake's food chain.

Initiation of Locomotion in Decerebrate Cats by Pulsed Magnetic Fields Projected onto Spinal Cord Segments - V. D. Avelev; R. Mathur; D. Behari; N. A. Shcherbakova; I. Yu. Dorofeev; A. A. Savokhin; Yu. P. Gerasimenko (Neuroscience and Behavioral Physiology, 2011)

An assessment of the potential impact of climate change on flood risk in Mumbai - Nicola Ranger; Stéphane Hallegatte; Sumana Bhattacharya; Murthy Bachu; Satya Priya; K. Dhore; Farhat Rafique; P. Mathur; Nicolas Naville; Fanny Henriet; Celine Herweijer; Sanjib Pohit; et al. (Climatic Change, 2011)

Occurrence of phthalic acid esters in Gomti River Sediment, India - Abhinav Srivastava; Vinod P. Sharma; Ranu Tripathi; Rakesh Kumar; Devendra K. Patel; Pradeep Kumar Mathur (Environmental Monitoring and Assessment, 2010)

Assessment of forest fragmentation in the conservation priority Dudhwa landscape, India using FRAGSTATS computed class level metrics - N. Midha; P. K. Mathur (Journal of the Indian Society of Remote Sensing, 2010)

Influence of cellular differentiation and elicitation on intermediate and late steps of terpenoid indole alkaloid biosynthesis in Catharanthus roseus - Ashutosh K. Shukla; Ajit K. Shasany; Ram K. Verma; Madan M. Gupta; Ajay K. Mathur; Suman P. S. Khanuja (Protoplasma, 2010)

Toward a Fuzzy Logic Control of the Infant Incubator - Narender P. Reddy; Garima Mathur; S. I. Hariharan (Annals of Biomedical Engineering, 2009)

Transient inhibitory effect of methoxychlor on testicular steroidogenesis in rat: an in vivo study - S. Vaithinathan; B. Saradha; P. P. Mathur (Archives of Toxicology, 2008)

Assessment and rationalization of genetic diversity of Papua New Guinea taro (Colocasia esculenta) using SSR DNA fingerprinting - D. Singh; E. S. Mace; I. D. Godwin; P. N. Mathur; T. Okpul; M. Taylor; D. Hunter; R. Kambuou; V. Ramanatha Rao; G. Jackson (Genetic Resources and Crop Evolution, 2008)

Distribution analysis of salt affected soils under canal and non-canal command area in a part of Etah district, U. P., using remote sensing technique - A. K. Singh; P. K. Singh; B. Lal; A. N. Singh; A. Mathur (Journal of the Indian Society of Remote Sensing, 2008)

Studies on the Genotoxicity of Endosulfan in Different Tissues of Fresh Water Fish Mystus vittatus Using the Comet Assay - Shilpi Sharma; N. S. Nagpure; Ravindra Kumar; Sanjay Pandey; Satish K. Srivastava; Poonam J. Singh; P. K. Mathur (Archives of Environmental Contamination and Toxicology, 2007)

Land cover classification using multi‐temporal MERIS vegetation indices - J. Dash; A. Mathur; G. M. Foody; P. J. Curran; J. W. Chipman; T. M. Lillesand (International Journal of Remote Sensing, 2007)

Himalayan glacier retreat using IRS 1C PAN stereo data - I. M. Bahuguna; A. V. Kulkarni; Shailesh Nayak; B. P. Rathore; H. S. Negi; P. Mathur (International Journal of Remote Sensing, 2007)

Qualitative and quantitative analysis of snow parameters using passive microwave remote sensing - V. D. Mishra; P. Mathur; R. P. Singh (Journal of the Indian Society of Remote Sensing, 2005)

Change detection study for snow covered mountains using remote sensing and ground based measurements - H. S. Negi; V. D. Mishra; P. Mathur (Journal of the Indian Society of Remote Sensing, 2005)

Chromosomal Instability in Callus Culture of Pisum sativum - P. Sanal Kumar; V.L. Mathur (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Sub-Surface Investigations on Deep Saline Groundwater of Charnockite Rock Formation, Kalpakkam, India - C. Gurumoorthy; P. Sasidhar; V. Arumugham; R. K. Mathur (Environmental Monitoring and Assessment, 2004)

Toxic Effects of Textile Printing Industry Effluents on Liver and Testes of Albino Rats - R. Krishnatrey; S. Sharma; K. P. Sharma; N. Mathur (Bulletin of Environmental Contamination and Toxicology, 2003)

2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) induces oxidative stress in the epididymis and epididymal sperm of adult rats - C. Latchoumycandane; K. C. Chitra; P. P. Mathur (Archives of Toxicology, 2003)

Persistent chlorinated pesticides and intra-uterine foetal growth retardation: a possible association - M. Siddiqui; S. Srivastava; S. Srivastava; P. Mehrotra; N. Mathur; I. Tandon (International Archives of Occupational and Environmental Health, 2003)

Induction of oxidative stress in the rat testis after short-term exposure to the organochlorine pesticide methoxychlor - C. Latchoumycandane; P. Mathur (Archives of Toxicology, 2002)

Effect of nonylphenol on the antioxidant system in epididymal sperm of rats - Chitra K.; Latchoumycandane C.; Mathur P. (Archives of Toxicology, 2002)

Cloning and characterization of an insecticidal crystal protein gene fromBacillus thuringiensis subspecieskenyae - Hari S. Misra; Nivedita P. Khairnar; Manjula Mathur; N. Vijayalakshmi; Ramesh S. Hire; T. K. Dongre; S. K. Mahajan (Journal of Genetics, 2002)

Field based spectral reflectance studies to develop NDSI method for snow cover monitoring - A V Kulkarni; J Srinivasulu; S S Manjul; Mathur P (Journal of the Indian Society of Remote Sensing, 2002)

Induction of oxidative stress in rat epididymal sperm after exposure to 2,3,7,8-tetrachlorodibenzo- p -dioxin - Latchoumycandane C.; Chitra K.; Mathur P. (Archives of Toxicology, 2002)

The Evolution of Enamel Microstructure: How Important Is Amelogenin? - Ajay Kishore Mathur; P. David Polly (Journal of Mammalian Evolution, 2000)

Isolation of two antifungal compounds fromNeolitsea cuipala and their activity against some plant pathogenic fungi - P. Boruah; P. Deka Bhuyan; S. C. Dutta; S. Mohan; R. K. Mathur (Folia Microbiologica, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Database management and analysis for CAPE project using remote sensing and GIS - Ajay Mathur; P K Litoria; P K Sharma; M H Kalubarme (Journal of the Indian Society of Remote Sensing, 1998)

Site suitability evaluation for locating sewage treatment plants using remote sensing and gis — a case study of phillaur and phagwara townships in punjab - P K Litoria; Ajay Mathur; P K Sharma; Charan kamal Singh (Journal of the Indian Society of Remote Sensing, 1997)